Heavy Metal Spatial Variation Mechanism and Ecological Health Risk Assessment in Volcanic Island Soils: A Case Study of Weizhou Island, China - Ran Bi; Wei Fu; Xuanni Fu (Land)
Heavy metals in volcanic island soils are key for assessing pollution risks and guiding environmental management strategies. However, research on heavy metals in volcanic island soils remains limited. In this study, the concentrations of heavy metals (Cu, Zn, Pb, Cr) in surface soil samples from Weizhou Island, China, were determined using ICP-OES, with average concentrations of 59.18 mg/kg, 119.06 mg/kg, 35.63 mg/kg, and 159.78 mg/kg, respectively. The basalt profiles generally exhibit higher heavy metal content and pH values compared to volcaniclastic rock profiles, as basalt accumulates higher concentrations of heavy metals. However, surface soils over volcaniclastic rocks show significantly higher heavy metal concentrations than those over basalt, indicating spatial variability in metal accumulation. Heavy metal concentrations in Weizhou Island soils are notably elevated at both the western wharf and the island’s tail, both characterized by volcaniclastic rock lithology, with human activities further increasing concentrations at the western wharf compared to the island’s tail. Land use types influence heavy metal content, with higher concentrations in abandoned land and lower concentrations in forest land with dense vegetation and organic matter. Principal component analysis reveals that heavy metals are primarily derived from natural parent material, with the first two principal components comprising 59.77% of the variance. Ecological risk assessment indicates that Weizhou Island soil is generally considered relatively clean, but Pb presents an ecological hazard, with 86.54% of the sites at risk. Overall, heavy metals in volcanic island soil mainly come from natural sources but lead contamination and human-impacted areas require attention.